"Simple Mucinous Cyst" of the Pancreas: A Clinicopathologic Analysis of 39 Examples of a Diagnostically Challenging Entity Distinct From Intraductal Papillary Mucinous Neoplasms and Mucinous Cystic Neoplasms. (January 2017) - Krasinskas, Alyssa M.; Oakley, Gerard J.; Bagci, Pelin; Jang, Kee-Taek; Kuan, Shih-Fan; Reid, Michelle D.; Erbarut, Ipek; Adsay, Volkan
Abstract : Pancreatic cysts >1 cm lined by nonpapillary mucinous epithelium without ovarian-type stroma pose diagnostic challenges. The term "simple mucinous cyst" was recently proposed for this entity. Our goal was to determine the clinicopathologic characteristics of these cysts, as they have not been previously described. Of the 39 patients with pancreatic resections included in this study, the mean age was 65 years and the female-to-male ratio was 4:1. The characteristics of the cysts are as follows: 82% had elevated cyst fluid carcinoembryonic antigen levels, 67% were unilocular, 69% occurred in the body/tail, 92% did not communicate with pancreatic ducts, the mean size was 2.4 cm (range, 1.0 to 5.5 cm), the cyst contents tended to be serous (48%) or viscous (28%), all had a smooth lining (only 1 had focal excrescences) composed of bland columnar mucinous epithelium (low-grade dysplasia) in 92% with focal high-grade dysplasia in 8%, and 65% had degenerative changes (granulation-like tissue, hemorrhage, and myxoid stroma). The cyst lining was CK7+ and 97% had a MUC5AC+ and/or MUC6+ gastric phenotype; overt intestinal features were absent. In total, 55% of cysts tested (fluid and/or resections) harbored KRAS mutations. The term "simple mucinous cyst" is useful to apply to >1 cm mucinous cysts that do not have characteristic features of intraductal papillary mucinous neoplasms or mucinous cystic neoplasms. KRAS mutations can be detected in these typically bland cysts, and in rare instances, focal high-grade dysplasia may be present. Hence, these cysts should be viewed as neoplastic and treated similarly to other mucinous pancreatic cysts.